2015
DOI: 10.1186/s13075-015-0545-1
|View full text |Cite
|
Sign up to set email alerts
|

Takayasu arteritis in childhood: retrospective experience from a tertiary referral centre in the United Kingdom

Abstract: IntroductionTakayasu arteritis (TA) is an idiopathic large-vessel vasculitis affecting the aorta and its major branches. Although the disease rarely affects children, it does occur, even in infants. The objective of this study was to evaluate the clinical features, disease activity, treatment and outcome of childhood TA in a tertiary UK centre.MethodsWe analysed a retrospective case series of children fulfilling the TA classification criteria of the European League against Rheumatism, the Paediatric Rheumatolo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
94
4
18

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 89 publications
(128 citation statements)
references
References 26 publications
(44 reference statements)
11
94
4
18
Order By: Relevance
“…Gender differences may be related to the role of estrogen or genetics [12]. The average time to diagnosis in our cohort was shorter than that reported previously [3, 9, 10, 13, 14], which may be due to pediatricians’ increased awareness of childhood TA in recent years, as well as regional differences. Tuberculosis infection is thought to be one factor underlying TA [15] and many researchers have reported the co-existence tuberculosis infection in those with TA [3, 14, 15].…”
Section: Discussionmentioning
confidence: 64%
“…Gender differences may be related to the role of estrogen or genetics [12]. The average time to diagnosis in our cohort was shorter than that reported previously [3, 9, 10, 13, 14], which may be due to pediatricians’ increased awareness of childhood TA in recent years, as well as regional differences. Tuberculosis infection is thought to be one factor underlying TA [15] and many researchers have reported the co-existence tuberculosis infection in those with TA [3, 14, 15].…”
Section: Discussionmentioning
confidence: 64%
“…Eleftheriou et al2 found permanent damage items on PVDI scoring in the follow-up (score ≥3) were associated with mortality ( P =0.024). Other factors such as the time to diagnosis >12 months, cardiac involvement, or need for biological therapy were not significantly associated 2…”
Section: Discussionmentioning
confidence: 98%
“…. Treatment was based on high-dose corticosteroids and immunosuppressive drugs (eg, methotrexate, azathioprine, and cyclophosphamide) 2,5,17…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Stenosis is irreversible and may result in severe complications including renovascular hypertension, severe claudication (limping), myocardial infarction and stroke. Early angioplasty is needed in patients with stenosis in renal arteries, aortic valve failure and stenosis in more than three sites (6)(7)(8)(9). Tosilizumab which was shown to be efficient in adult studies has been reported to be also efficient in pediatric TA cases in case reports (15,16).…”
Section: Takayasu Arteritismentioning
confidence: 99%